When Distance Disappears: Inventors, Education, and the Locus of Knowledge Spillovers - Giuri, Paola; Mariani, Myriam (The Review of Economics and Statistics, 2013)
This paper discusses the role of education in shaping the geographical breadth of knowledge spillovers. Data pertaining to 6,051 European inventions reveal that inventors with a high level of education, such as a university or doctoral degree, rely more on external spillovers regardless of the geographical location of their sources. Controlling for this effect, they also access geographically wider knowledge spillovers. This result holds after controlling for alternative explanations, such as the inventors' network and the site where the research is performed. By contributing to individual openness, education thus provides a means to break through geographical barriers to attain knowledge diffusion.